Titanium dioxide loaded metal composite material as well as preparation method and application thereof

A titanium dioxide nanoarray supports rhodium nanoparticles on a titanium substrate, addressing the agglomeration and stability issues of rhodium catalysts, enhancing catalytic performance in hydrogen evolution reactions and fuel cells.

CN119121313AActive Publication Date: 2024-12-13WUYI UNIV

Patent Information

Application Number
CN202411168671.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
2044-08-23

Smart Images

  • Figure CN119121313A_ABST
    Figure CN119121313A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium dioxide loaded metal composite material and a preparation method and application thereof, the titanium dioxide loaded metal composite material comprises a titanium substrate and a titanium dioxide nano array, and the titanium dioxide nano array grows on the surface of the titanium substrate; the titanium dioxide nano array is composed of titanium dioxide nano rods; metal rhodium nanoparticles are loaded on the surface of the titanium dioxide nanorod. The rhodium nanoparticles can be fully exposed on the outer surface by utilizing the structure of the titanium dioxide three-dimensional nano array, so that the active surface area of the rhodium nanoparticles is greatly increased, and the activity of the titanium dioxide loaded metal composite material as a hydrogen evolution reaction catalyst is improved. According to the preparation method of the composite material, ethylene glycol is adopted as a reaction solvent, the prepared titanium dioxide nano array has three-dimensional anisotropy and high stability, and a large surface area and a complex electron transmission path are provided; and then the rhodium nanoparticles are loaded by a wet chemical method, so that the catalytic activity of the rhodium nanoparticles is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a titanium dioxide-loaded metal composite material and a preparation method and application thereof. Background Art

[0002] Hydrogen is a clean energy source with the greatest potential to replace fossil fuels. Hydrogen production by water electrolysis is an effective way to produce hydrogen efficiently, with the characteristics of green environmental protection, flexible production and high product purity. In the process of water electrolysis, the selection of highly active cathode hydrogen evolution reaction (HER) catalysts is crucial to improving the efficiency of water electrolysis. At present, catalysts for hydrogen production by water electrolysis are mainly divided into three categories: precious metals, transition metals and non-metals. Precious metal catalysts mainly refer to Pt group metals and their alloys. Precious metal catalysts can effectively reduce the overpotential of the HER reaction and have excellent catalytic performance, but their reserves are extremely low, the cost is high, and the electrochemical stability is poor, which limits their large-scale industrial application. Among them, the precious metal rhodium (Rh) has high electrochemical activity and a lower price than Pt, but its disadvantage is that it is easy to agglomerate and has poor stability. Therefore, how to improve the shortcomings of the precious metal rhodium that it is easy to agglomerate and has poor stability is an urgent problem to be solved. Summary of the invention

[0003] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a titanium dioxide-loaded metal composite material. The second purpose of the present invention is to provide a method for preparing the above-mentioned titanium dioxide-loaded metal composite material. The third purpose of the present invention is to provide an application of the above-mentioned titanium dioxide-loaded metal composite material. The fourth purpose of the present invention is to provide a membrane electrode.

[0004] The present invention adjusts the electronic structure of the precious metal through a transition metal-based support, and utilizes the structure of a three-dimensional titanium dioxide nanoarray to fully expose the precious metal rhodium on the outer surface, thereby greatly increasing its active surface area, improving the atomic utilization rate and stability of the precious metal rhodium, and avoiding agglomeration, thereby improving the activity of the hydrogen evolution reaction catalyst. In addition, in the preparation method, by directly depositing rhodium on the substrate, the use of an adhesive can be avoided, thereby reducing mass transfer resistance and reducing stratification.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a titanium dioxide loaded metal composite material, comprising a titanium substrate, a titanium dioxide nanoarray grown on the surface of the titanium substrate; the titanium dioxide nanoarray is composed of titanium dioxide nanorods; and the surface of the titanium dioxide nanorods is loaded with metal rhodium nanoparticles.

[0007] Preferably, the titanium substrate is titanium foam or titanium sheet.

[0008] More preferably, the shape of the titanium foam or titanium sheet is square or circular. Further preferably, the square length of the square is ≤380 mm, and the square width is ≤380 mm. Further preferably, the diameter of the circle is ≤380 mm.

[0009] More preferably, the thickness of the titanium substrate is 1 to 5 mm.

[0010] Preferably, the diameter of the titanium dioxide nanorods is 10 to 30 nm.

[0011] Preferably, the metal rhodium nanoparticles are spherical nanoparticles. More preferably, the particle size of the metal rhodium nanoparticles is 2-5 nm.

[0012] The second aspect of the present invention provides a method for preparing the titanium dioxide-loaded metal composite material according to the first aspect, comprising the following steps:

[0013] S1, mixing ethylene glycol, hydrochloric acid and a titanium substrate, and performing a solvothermal reaction 1 to obtain a material in which a titanium dioxide nanoarray is grown on the surface of the titanium substrate;

[0014] S2, mixing the composite material of S1, ethylene glycol, urea and a rhodium source, and performing a solvent thermal reaction 2 to obtain the titanium dioxide-supported metal composite material.

[0015] Preferably, in step S1, the volume ratio of ethylene glycol to hydrochloric acid is (10-20):1.

[0016] More preferably, in step S1, the volume ratio of ethylene glycol to hydrochloric acid is (13-17):1.

[0017] Preferably, in step S1, the reaction temperature of the solvent thermal reaction 1 is 180-220°C, and the reaction time is 16-24h.

[0018] More preferably, in step S1, the reaction temperature of the solvent thermal reaction 1 is 180-210°C, and the reaction time is 18-22h.

[0019] Preferably, step S1 further comprises the following steps: after the solvent thermal reaction 1, collecting the solid product, washing and drying the solid product to obtain the titanium dioxide-supported metal composite material.

[0020] More preferably, the drying temperature is 50-70° C. and the drying time is 5-7 hours.

[0021] Preferably, in step S2, the molar ratio of urea to rhodium atoms in the rhodium source is (30-40):1.

[0022] Preferably, the rhodium source is a soluble rhodium salt.

[0023] More preferably, the rhodium source is rhodium chloride hydrate.

[0024] Preferably, in step S2, the usage ratio of urea to ethylene glycol is (300-400) mmol:1L.

[0025] Preferably, in step S2, the reaction temperature of the solvent thermal reaction 2 is 140-180°C, and the reaction time is 10-14h.

[0026] More preferably, in step S2, the reaction temperature of the solvent thermal reaction 2 is 150-170° C., and the reaction time is 11-13 h.

[0027] The third aspect of the present invention provides the use of the titanium dioxide-supported metal composite material described in the first aspect in a hydrogen evolution reaction catalyst.

[0028] The fourth aspect of the present invention provides a membrane electrode, which comprises a proton exchange membrane, a catalyst layer, and a diffusion layer stacked in sequence; the catalyst layer comprises the titanium dioxide-loaded metal composite material described in the first aspect.

[0029] The beneficial effects of the present invention are:

[0030] The invention provides a titanium dioxide-loaded metal composite material, wherein a titanium dioxide nanoarray is grown on a titanium substrate, and a transition metal main body of a three-dimensional structure is constructed in situ; the titanium dioxide nanoarray is composed of titanium dioxide nanorods, and metal rhodium nanoparticles are loaded on the surface of the nanorods. The structure of the three-dimensional titanium dioxide nanoarray can fully expose the rhodium nanoparticles on the outer surface, thereby greatly increasing the active surface area, thereby improving the activity of the titanium dioxide-loaded metal composite material as a hydrogen evolution reaction catalyst.

[0031] Specifically, compared with the prior art, the present invention also has the following advantages:

[0032] 1. The present invention also provides a method for preparing a titanium dioxide-loaded metal composite material. First, a titanium dioxide nanoarray is in situ grown on a titanium substrate. Ethylene glycol is used as a reaction solvent, which is beneficial to improving the stability of the product. The prepared titanium dioxide nanoarray has three-dimensional anisotropy, provides a larger surface area and a more complex electron transmission path; then, a wet chemical method is used to load precious metal rhodium nanoparticles, and the rhodium nanoparticles are fully exposed on the outer surface of the titanium dioxide three-dimensional nanoarray, so that the active surface area is greatly increased, thereby improving the catalytic activity of the rhodium nanoparticles.

[0033] 2. The present invention also provides the use of titanium dioxide-supported metal composite materials in hydrogen evolution reaction catalysts, wherein rhodium has high catalytic activity for hydrogen evolution reaction and extremely high corrosion resistance to various electrolytes; the structure of the titanium dioxide three-dimensional nanoarray is utilized to fully expose rhodium nanoparticles on the outer surface, thereby greatly increasing the active surface area, being able to reduce the overpotential in acidic, neutral and alkaline electrolytes, and improving the catalytic performance of the hydrogen evolution catalyst; it can exhibit high catalytic activity and stability when applied to acidic and alkaline hydrogen evolution, and has great application potential in membrane electrode and hydrogen fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a scanning electron microscope image of the Ti / TiO2 material in Example 1;

[0035] Figure 2 is a scanning electron microscope image of the Ti / TiO2 material in Example 1 at another viewing angle;

[0036] Figure 3 It is a transmission electron microscope image of the Ti / TiO2 material in Example 1;

[0037] Figure 4 is a scanning electron microscope image of the Ti / TiO2 material in Example 2;

[0038] Figure 5 This is a scanning electron microscope image of the Ti / TiO2 material in Comparative Example 1;

[0039] Figure 6 This is a scanning electron microscope image of the Ti / TiO2 material in Comparative Example 1 at another viewing angle;

[0040] Figure 7 This is a scanning electron microscope image of the Ti / TiO2 material in Comparative Example 2;

[0041] Figure 8 This is a scanning electron microscope image of the Ti / TiO2 material in Comparative Example 3;

[0042] Fig. 9 This is a scanning electron microscope image of the Ti / TiO2 material in Comparative Example 4;

[0043] Fig.10 The physical pictures of different Ti / TiO2 materials of Example 1 and Comparative Examples 1-4;

[0044] Fig.11 is the XRD pattern of the Ti / TiO2 material in Example 1;

[0045] Fig.12 is a scanning electron microscope image of the Ti / TiO2-Rh composite material in Example 1;

[0046] Fig.13 is a transmission electron microscope image of the Ti / TiO2-Rh composite material in Example 1;

[0047] Fig.14 The catalytic performance of the Ti / TiO2-Rh composite materials of Examples 1, 3 and 4 in an acidic hydrogen evolution reaction;

[0048] Fig.15 The catalytic performance of the Ti / TiO2-Rh composite materials of Examples 1, 3 and 4 in alkaline hydrogen evolution reaction;

[0049] Fig.16 The catalytic performance of the Ti / TiO2-Rh composite materials of Example 1 and Comparative Examples 2-4 in acidic hydrogen evolution reaction;

[0050] Fig.17 The catalytic performance of the Ti / TiO2-Rh composite materials of Example 1 and Comparative Examples 2-4 in alkaline hydrogen evolution reaction;

[0051] Fig.18 The catalytic performance of the Ti / TiO2-Rh composite materials of Examples 1-2 and Comparative Example 5 in an acidic hydrogen evolution reaction;

[0052] Fig.19 The catalytic performance of the Ti / TiO2-Rh composite materials of Examples 1-2 and Comparative Example 5 in alkaline hydrogen evolution reaction. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.

[0054] Example 1

[0055] This embodiment provides a titanium dioxide-loaded metal composite material, and the preparation method is as follows:

[0056] (1) 15 mL of ethylene glycol (EG), 1 mL of hydrochloric acid and 2 cm×3 cm of titanium foam were sequentially added to a reactor and mixed; the reactor containing the mixture was placed in an oven, heated to 200°C, and maintained for 20 h; after the reaction was completed, the reactor was cooled to room temperature, the solid product was collected and washed, and the sample was placed in an oven at 60°C and maintained for 6 h for drying to obtain a material with titanium dioxide nanoarrays grown on the surface of a titanium substrate, which was recorded as Ti / TiO2 material;

[0057] (2) The composite material was cut into 1 cm × 2 cm pieces, and the composite material, 6 mL of ethylene glycol, 2.04 mmol of urea and 0.06 mmol of rhodium chloride trihydrate were added to a round-bottom flask in sequence and mixed, and the rhodium salt was dissolved by stirring. The round-bottom flask was placed in an oil bath, and the oil bath was heated from room temperature to 160 ° C and maintained for 12 h to obtain the titanium dioxide-loaded metal composite material, which was recorded as Ti / TiO2-Rh composite material.

[0058] Example 2

[0059] This embodiment provides a titanium dioxide-loaded metal composite material and a preparation method thereof, and the preparation method thereof is similar to that of embodiment 1. The difference is that the titanium foam is replaced by a titanium sheet.

[0060] Example 3

[0061] This embodiment provides a titanium dioxide-supported metal composite material and a preparation method thereof, and the preparation method thereof is similar to that of Example 1. The difference is that the reaction time in step (2) is replaced from 12 h to 10 h.

[0062] Example 4

[0063] This embodiment provides a titanium dioxide-supported metal composite material and a preparation method thereof, and the preparation method thereof is similar to that of Example 1. The difference is that the reaction time in step (2) is replaced from 12 h to 14 h.

[0064] Comparative Example 1

[0065] The preparation method of this comparative example is similar to that of Example 1, except that 15 mL of ethylene glycol in step (1) is replaced by 12 mL of ethylene glycol and 3 mL of water.

[0066] Comparative Example 2

[0067] The preparation method of this comparative example is similar to that of Example 1, except that 15 mL of ethylene glycol in step (1) is replaced by 7.5 mL of ethylene glycol and 7.5 mL of water.

[0068] Comparative Example 3

[0069] The preparation method of this comparative example is similar to that of Example 1, except that 15 mL of ethylene glycol in step (1) is replaced by 3 mL of ethylene glycol and 12 mL of water.

[0070] Comparative Example 4

[0071] The preparation method of this comparative example is similar to that of Example 1, except that 15 mL of ethylene glycol in step (1) is replaced by 15 mL of water.

[0072] Comparative Example 5

[0073] This comparative example provides a titanium-loaded metal composite material, and its preparation method is:

[0074] A metal Ti sheet was used, and the upper Ti sheet was cut into 1 cm×2 cm. The Ti sheet, 6 mL of ethylene glycol, 2.04 mmol of urea and 0.06 mmol of rhodium chloride trihydrate were added into a round-bottom flask in sequence and mixed. The rhodium salt was dissolved by stirring. The round-bottom flask was placed in an oil bath, and the oil bath was heated from room temperature to 160°C and maintained for 12 hours to obtain the titanium dioxide-loaded metal composite material, which was recorded as a Ti-Rh composite material.

[0075] Material characterization

[0076] Figure 1 and Figure 2 is a scanning electron microscope (SEM) image of the Ti / TiO2 material in Example 1; Figure 3 is a transmission electron microscope (TEM) image of the Ti / TiO2 material in Example 1; Figure 4 is a scanning electron microscope image of the Ti / TiO2 material in Example 2; Figure 1-4 It can be seen that the nanorods arrayed by solvothermal method using ethylene glycol and hydrochloric acid are well arranged, smaller in size, and have a larger specific surface area. Figure 5-9 This is a scanning electron microscope image of the Ti / TiO2 array material in Comparative Examples 1-4. As the amount of water increases, the size of the arrayed TiO2 gradually becomes wider and uneven, and the TiO2 array layer gradually becomes thicker, resulting in a decrease in electrochemical performance.

[0077] Fig.10 The actual pictures of different Ti / TiO2 materials of Example 1 and Comparative Examples 1-4 show that the titanium foam prepared by adding only water is almost broken and cannot be used for subsequent electrochemical tests, while the product of Example 1 using ethylene glycol as the reaction solvent is the most complete.

[0078] Fig.11 is the XRD pattern of the Ti / TiO2 material in Example 1;

[0079] Fig.12 is a scanning electron microscope image of the composite material in Example 1; Fig.13 is a transmission electron microscope image of the composite material in Example 1; Figure 3 and Fig.13 It can be seen that the metal rhodium nanoparticles are loaded on the titanium dioxide nanorods. Fig.12 It can be seen that titanium dioxide nanorods loaded with metal rhodium nanoparticles form a nanoarray.

[0080] Experimental analysis

[0081] The products of Examples 1-4 and Comparative Examples 2-5 were subjected to a hydrogen evolution test method, and the specific test method and results are as follows:

[0082] 1. The test method includes the following steps: (1) Preparation of working electrode: The sample is clamped in a platinum electrode clamp, 1cm·1cm is immersed in the electrolyte, and then the electrocatalytic test is performed. (2) Acid performance test: A three-electrode test method is used, with a platinum electrode clamp containing catalyst TiO2 / Rh as the working electrode, a reference electrode as saturated calomel, a counter electrode as a carbon rod, and an electrolyte as 0.5mol / L H2SO4 solution, and a linear sweep method (LSV) test. The LSV test range is 0.1V to 0.45V, and the scanning speed is 5mV / s. (3) Alkaline performance test: A three-electrode test method is used, with a platinum electrode clamp containing catalyst TiO2 / Rh as the working electrode, a reference electrode as saturated calomel, a counter electrode as a carbon rod, and an electrolyte as 1mol / L KOH solution, and a linear sweep method (LSV) test.

[0083] 2. Fig.14 The catalytic performance of the composite materials of Examples 1, 3 and 4 in an acidic hydrogen evolution reaction; Fig.15 The catalytic performance of the composite materials of Examples 1, 3 and 4 in alkaline hydrogen evolution reaction is analyzed. Fig.14 and 15 The overpotentials of the composite materials of Examples 1, 3 and 4 at different current densities in the acidic / alkaline hydrogen evolution reaction catalysis can be obtained, and the results are shown in Table 1:

[0084] Table 1

[0085] <![CDATA[Acidic 10 mA·cm -2 > <![CDATA[Acidic 50 mA·cm -2 > <![CDATA[Alkaline 10 mA·cm -2 > <![CDATA[Alkaline 50 mA·cm -2 > Example 1 24 72 37 75 Example 3 48 85 54 179 Example 4 55 89 50 164

[0086] In the acid LSV test, the product of Example 1 has a -2 The overpotential is only 24 mV at 50 mA cm -2 The overpotential is only 72 mV when the -2 The overpotential is only 37mV at 50mAcm -2 The overpotential at that time was only 75 mV. The test results showed that the overpotential of the product obtained by reacting for 12 hours in step (2) was low and the electrochemical performance was the best.

[0087] 3. Fig.16 The catalytic performance of the composite materials of Example 1 and Comparative Examples 2-4 in acidic hydrogen evolution reaction; Fig.17 The catalytic performance of the composite materials of Example 1 and Comparative Examples 2-4 in alkaline hydrogen evolution reaction is analyzed. Fig.16 and 17 The overpotentials of the composite materials of Example 1 and Comparative Examples 2-4 at different current densities in the acidic / alkaline hydrogen evolution reaction catalysis can be obtained, and the results are shown in Table 2:

[0088] Table 2

[0089] <![CDATA[Acidic 10 mA·cm -2 > <![CDATA[Acidic 50 mA·cm -2 > <![CDATA[Alkaline 10 mA·cm -2 > <![CDATA[Alkaline 50 mA·cm -2 > Example 1 24 72 37 75 Comparative Example 2 Poor performance Poor performance Poor performance Poor performance Comparative Example 3 51 98 104 none Comparative Example 4 Poor performance Poor performance 121 none

[0090] Note: The corresponding voltage range in the graph cannot be read if the performance is poor or non-existent.

[0091] It can be seen from the LSV test that the precious metal rhodium loaded on the full EG and hydrochloric acid arrays exhibit excellent performance under acid-base conditions, while the precious metal rhodium loaded on TiO2 of other ratio arrays exhibit poor electrochemical performance and cannot be used for electrocatalytic reactions.

[0092] 4. Fig.18 The catalytic performance of the composite materials of Examples 1-2 and Comparative Example 5, and the intermediate product (Ti / TiO2 material) of Examples 1-2 in an acidic hydrogen evolution reaction; Fig.19 The catalytic performance of the composite materials of Examples 1-2 and Comparative Example 5, and the intermediate products of Examples 1-2 in alkaline hydrogen evolution reaction; Fig.18 and 19 The overpotentials of the composite materials of Examples 1-2 and Comparative Example 5, and the intermediate products of Examples 1-2 at different current densities in the acidic / alkaline hydrogen evolution reaction catalysis can be obtained, and the results are shown in Table 3:

[0093] Table 3

[0094]

[0095] It can be seen from the LSV test that rhodium has high catalytic activity for hydrogen evolution reaction and extremely high corrosion resistance to various electrolytes; it can be seen from the comparison between Example 1 and Comparative Example 5 that the structure of the titanium dioxide three-dimensional nanoarray is used to fully expose the rhodium nanoparticles on the outer surface, so that the active surface area is greatly increased, the overpotential in acidic and alkaline electrolytes can be reduced, and the catalytic performance of the hydrogen evolution catalyst is improved. It can be applied to acidic hydrogen evolution and alkaline hydrogen evolution to show high catalytic activity and stability, and has great application potential in membrane electrode and hydrogen fuel cells.

[0096] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A titanium dioxide-loaded metal composite material, characterized in that: The invention comprises a titanium substrate, on the surface of which a titanium dioxide nano-array is grown; the titanium dioxide nano-array is composed of titanium dioxide nano-rods; and on the surface of the titanium dioxide nano-rods are loaded metal rhodium nano-particles.

2. The titanium dioxide-loaded metal composite material according to claim 1, characterized in that: The titanium substrate is foamed titanium or a titanium sheet.

3. The method for preparing the titanium dioxide-loaded metal composite material according to claim 1 or 2, characterized in that: The steps include: S1, mixing ethylene glycol, hydrochloric acid and a titanium substrate, and performing a solvothermal reaction 1 to obtain a material in which a titanium dioxide nanoarray is grown on the surface of the titanium substrate; S2, mixing the product of S1, ethylene glycol, urea and a rhodium source, and performing a solvent thermal reaction 2 to obtain the titanium dioxide-supported metal composite material.

4. The method for preparing a titanium dioxide-loaded metal composite material according to claim 3, characterized in that: In step S1, the volume ratio of ethylene glycol to hydrochloric acid is (10-20):

1.

5. The method for preparing a titanium dioxide-loaded metal composite material according to claim 3, characterized in that: In step S1, the reaction temperature of the solvent thermal reaction 1 is 180-220°C, and the reaction time is 16-24h.

6. The method for preparing a titanium dioxide-loaded metal composite material according to claim 3, characterized in that: In step S2, the molar ratio of urea to rhodium atoms in the rhodium source is (30-40):1; And / or, the rhodium source is a soluble rhodium salt.

7. The method for preparing a titanium dioxide-supported metal composite material according to claim 3, characterized in that: In step S2, the usage ratio of urea to ethylene glycol is (300-400) mmol:1L.

8. The method for preparing a titanium dioxide-loaded metal composite material according to claim 3, characterized in that: In step S2, the reaction temperature of the solvent thermal reaction 2 is 140-180°C, and the reaction time is 10-14h.

9. Use of the titanium dioxide-supported metal composite material according to claim 1 or 2 in preparing a catalyst for hydrogen evolution reaction.

10. A membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane, a catalyst layer and a diffusion layer which are stacked in sequence; the catalyst layer comprises the titanium dioxide-loaded metal composite material according to claim 1 or 2.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide hierarchical nano-tube ordered array consisting of controllable-morphology anatase single-crystal particles

    CN102644111A

  • Preparing method for in-site growth of titanium dioxide nanometer array film on surface of metal

    CN105671531A

  • Method for preparing metal-rhodium nanoparticle modified titanium dioxide nanotube array photocatalytic material

    CN107413338A

  • Method for preparing self-supporting titanium dioxide loaded noble metal catalyst

    CN111744471A

  • Pretreatment method of titanium substrate for electrode

    CN113265698A

Cited By

  • Organic phosphonic acid modified three-dimensional porous titanium dioxide catalyst as well as preparation method and application thereof

    CN122424803A